2012
DOI: 10.1039/c2cp23098d
|View full text |Cite
|
Sign up to set email alerts
|

The trehalose coating effect on the internal protein dynamics

Abstract: (15)N and (13)C NMR experiments were applied to conduct a comparative study of a cold shock protein (Csp) in two states-lyophilized powder and a protein embedded in a glassy trehalose matrix. Both samples were studied at various levels of rehydration. The experiments used (measuring relaxation rates R(1) and R(1ρ), motionally averaged dipolar couplings and solid state exchange method detecting reorientation of the chemical shift anisotropy tensor) allow obtaining abundant information on the protein structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…A liquid-state NMR studies of the temperature dependences of the order parameters (Chang and Tjandra 2005;Johnson et al 2007) demonstrate that these dependences are rather strong at temperatures above 35°C, and within the range from 12 to 27°C (the limiting temperatures of our experiments), the S 2 variation is just slightly above the experimental error. Solid state NMR measurements of the 1 H-15 N dipolar coupling in amorphous lyophilized rehydrated protein powders (Hackel et al 2012) show no experimentally detectable difference between 10 and 25°C at all. Thus, we conclude that neglecting the temperature dependence of the order parameters within the narrow temperature range does not cause any essential error in the fitting.…”
Section: Correlation Functions and Spectral Densitiesmentioning
confidence: 90%
“…A liquid-state NMR studies of the temperature dependences of the order parameters (Chang and Tjandra 2005;Johnson et al 2007) demonstrate that these dependences are rather strong at temperatures above 35°C, and within the range from 12 to 27°C (the limiting temperatures of our experiments), the S 2 variation is just slightly above the experimental error. Solid state NMR measurements of the 1 H-15 N dipolar coupling in amorphous lyophilized rehydrated protein powders (Hackel et al 2012) show no experimentally detectable difference between 10 and 25°C at all. Thus, we conclude that neglecting the temperature dependence of the order parameters within the narrow temperature range does not cause any essential error in the fitting.…”
Section: Correlation Functions and Spectral Densitiesmentioning
confidence: 90%
“…Since the proton distribution in the samples did not correlate with the corresponding distribution of relaxation times, it was suggested that sugar molecules partition between sugar-only and protein-sugar phases, in agreement with above reported SAXS and Raman results. NMR experiments were performed also on a cold shock protein embedded in a glassy trehalose matrix, at various levels of hydration [177]. The protein structure was found more native in trehalose than in dehydrated lyophilized powders; nanosecond and microsecond time scales motions of N-H groups become slower, and on rehydration water molecules build up around proteins forming a layer at the protein-matrix interface.…”
Section: Meso-and Macroscopic Levelmentioning
confidence: 99%
“…DIPSHIFT is a so-called constant-time experiment, meaning that the t1 time is increased at the expense of the following heteronuclear decoupling period, and ranges from 0 to one rotor period τR=1/νR. The functional form of Sfalse(t1false) can be described by analytical formulae based on Average-Hamiltonian theory; they enable the determination of the dipolar couplings from fitting the experimentally obtained Sfalse(t1false) curves [78,79,80]. For a CH group S(t1)/S(0)=false〈prefixcosϕfalse〉β,γ3.33333pt, and for a CH 2 group S(t1)/S(0)=false〈prefixcosϕ1prefixcosϕ2false〉α,β,γ3.33333pt, where the averages are over the Euler angles α,β and γ transforming the dipolar tensor components in the principal axis frame to the tensor components in the laboratory frame, and the phase angles depend on the C–H dipolar coupling strength and on the MAS frequency used.…”
Section: Dynamic Order Parameters In Lipid Membranesmentioning
confidence: 99%
“…Explicit expressions for the ϕiDres, which are phase factors related to the time integral of the dipolar tensor as modulated by the MAS, are given e.g., in refs. [78,80].…”
Section: Dynamic Order Parameters In Lipid Membranesmentioning
confidence: 99%